Hypoglycemic flavonoids from Selaginella tamariscina (P.Beauv.) Spring. (March 2022) - Long, Hong-Ping; Liu, Jian; Xu, Ping-Sheng; Xu, Kang-Ping; Li, Jing; Tan, Gui-Shan
Abstract: Six flavonoids, namely, three undescribed biflavonoids, one undescribed 8-aryl flavonoid, and two known compounds, were isolated from Selaginella tamariscina (P.Beauv.) Spring. The structures and absolute configurations of those undescribed compounds were established by NMR spectroscopy data, HRESIMS analyses and electronic circular dichroism (ECD) analyses. In addition, all the isolates were evaluated for their hypoglycemic activity in HepG2 cells. Involvenflavone H, I, and J significantly increased glucose consumption in both normal and insulin-resistant HepG2 cells. Interestingly, these three compounds can effectively upregulate the protein expression of glucokinase (GCK) and adenylate cyclases (ADCYs). These results suggested that involvenflavone H, I, and J (especially involvenflavone J) may have potent hypoglycemic activity, which also provided promising molecular targets for the treatment of diabetes. Graphical abstract: Image 1 Highlights: Four undescribed flavonoids were isolated from Selaginella tamariscina (P.Beauv.) Spring. Involvenflavone H, I, and J significantly increased the glucose consumption in insulin-resistant HepG2 cells. Involvenflavone J up-regulated the protein expression of glucokinase and adenylate cyclases effectively.